Analysis of Saturated Capacity on the Runway Based on Advisory Circular 150/5060-5 As a Study Material for Airport Management Learning - I Gusti Agung Ayu Mas Oka; Dwi Chandra Yuniar; Dian Anggraini Purwaningtyas; Nabilla Azzahra (Journal of Innovation in Educational and Cultural Research, 2022)
The demand for air transportation from year to year until 2018 continues to increase. However, in 2019 it decreased as a result of the increase in air ticket fares, as well as in 2020 as a result of the COVID-19 pandemic. Although demand is experiencing a decline, knowing airport capacity is important in airport planning, which is one of the disciplines studied in airport management. Therefore, this research aims to estimate the saturation capacity of the runway at Sultan Mahmud Badaruddin International Airport (SMB) II, using the method developed by the Federal Aviation Administration (FAA) and specified in the Advisory Circular 150/5060-5. The results of this study can be used as study material in learning the field of airport management science. Based on the data obtained and processed, the results show that the saturation capacity of the runway per hour for runway 11 directions is 53 for Visual Flight Rules (VFR) and 49 Instrument Flight Rules (IFR). Meanwhile, the direction of runway 29 is 50 in VFR conditions and 46 in IFR conditions. So that the average saturation capacity for both runway directions is 51 in VFR conditions and 48 in IFR conditions. This runway capacity calculation method cannot accommodate differences in the flight separation rules applied, so that this capacity will be achieved if Airnav Indonesia, Palembang Branch as the manager of flight navigation services at SMB II Airport applies the same rules as the FAA. The currently applied separation rules are relatively larger than those set by the International Civil Aviation Organization (ICAO) and also the FAA. As an ICAO member country, it is still possible to lower the separation rules set by ICAO to increase runway capacity.The conclusions of the research have been obtained from the analysis of the saturated capacity of the runway based on the advisory circular 150/5060-5 which has been used as a study material for learning in the field of airport management science.